Campus sustainability at Rhodes University, South Africa: perceptions, awareness level, and potential interventions - Thondhlana, Gladman; Nkosi, Baby-Sandile (Frontiers in Sustainability, 2024)
With an increasing environmental footprint due to resource consumption by employees and students, universities have a moral responsibility to integrate sustainability principles in daily university operations as part of broader societal contributions. Understanding perceptions of sustainability and awareness level can inform universities about their performance on sustainability matters, and allocation of financial and human resources needed to help universities achieve their intended sustainability targets. However, studies on perceptions regarding campus daily sustainability practices, organisational culture and role of leadership are scarce. To address this gap, this study examined staff and students' perceptions of campus sustainability, including their views on daily operations, sustainability priorities, the organisation's level of commitment towards sustainability goals and the role of top management in promoting sustainable practices at Rhodes University, South Africa. The findings show low and varied level of sustainability awareness between stakeholders and a disconnect between campus sustainability efforts and priorities, suggestive of a policy-implementation gap. The respondents cited lack of funding, cooperation, and commitment from top leadership as the key barriers to campus sustainability. The findings point to the need to rethink the sustainability challenges universities face and ways of addressing them. Possible strategies for improving perceptions include raising awareness on campus sustainability through engagements, engendering a sustainability culture, clearly defining responsibilities for overseeing sustainability matters, co-designing sustainability goals and implementation strategies, and the need to monitor and report progress made towards achieving sustainability goals.